Penyajian Ruang Pamer Sejarah Museum Bank Indonesia Dengan Teknik Pencahayaan Teatrikal - Rizki, Muhamad Fadhlin; Nazhar, Ryanty Derwentyana (Fakultas Desain Universitas Komputer Indonesia, 2021)
The museum is a place that displays objects related to history and a means of research and recreation. The object that is patched has a museum that has information that must be conveyed to visitors. The layout of the exhibits in the museum room is a factor that must be considered so that communication between the exhibitors and visitors can run smoothly. The layout can make it easier for visitors to find information enjoying the objects shown. Another factor that helps to attract people's interest to enjoy these objects is the lighting technique. The use of theatrical techniques in museums can attract the interest of the public, also can give another impression that will be captured by visitors here. The Bank Indonesia Museum located in Jakarta is a museum that shows the development of banks in Indonesia. By using a case study method through visual analysis of lighting, the lighting techniques in this room will be polished the impression conveyed to visitors.